Natural Occurrence and Isolation of Ampelomyces quisqualis (mycoparasite) Associated with Rose, Other Powdery Mildew Infecting Host Plants in Himachal Pradesh, India - Vijay Kumar; Sunita Chandel (International Journal of Fungi, 2024)
The presence of Ampelomyces spp. was quantified in naturally occurring powdery mildew infecting rose plants during the year 2015–2016. Powdery mildew infected rose samples were collected from the different rose-growing areas of Himachal Pradesh during the months of April–June and September–November. Relationships between Ampelomyces and Podosphaera pannosa were reported in four areas between September and November. Bilaspur, Mandi, Shimla, and Solan. However, there was no occurrence of Ampelomyces quisqualis in districts of Kangra and Sirmour during the present study. Nine different powdery mildew infected hosts were studied, out of which only three hosts have shown the association with A. quisqualis, which were Chotta dhatura (September–November), Zinnia and Dahlia (May–July) at Nauni. However, occurrence of A. quisqualis was reported from different powdery mildew host but it can only be isolated from Xanthium strumarium (Chota Dhatura) The effect of solid media on mycelial growth, production of pycnidium, size, shape, and color of pycnidium and conidia of A. quisqualis was investigated and maximum average mycelial growth (28.26 mm) was reported in malt extract medium followed by the Oat Meal Agar medium (22.33 mm) and Potato Dextrose Agar medium (18.50 mm).
Keywords: Ampelomyces quisqualis; Fungus; Powdery mildew; mycoparasite; rose